Structure and anticoagulant activity of a galactoarabinan sulfate polysaccharide and its oligosaccharide from the green algae, Codium fragile - Peipei, Li; Qinghong, Zhang; Yin, Chen; Pengfei, He; Junjie, Zeng (International journal of biological macromolecules, 2024)
A polysaccharide, CZS-0-1, was obtained from the marine green algae Codium fragile using ion-exchange and size-exclusion chromatography. Composition and characteristics analyses showed CZS-0-1 was a sulfated galactoarabinan consisting of arabinose, galactose and a small amount of glucose in a ratio of 9:2:1 with 21% sulfate content and a molecular weight of 810 kDa. Structural properties were determined using desulfation and methylation analyses combined with instrument analysis. The results showed that the backbone of CZS-0-1 was (1 → 3)-β-L-Arap. Its O-4 and/or O-2 positions showed sulfate modification; additionally, it had 10% of (1 → 3)-β-D-Galp branches at the O-4 position of the (1 → 3)-β-L-Arap. The galactose side chains also had sulfate modification at the O-4 or O-6 position. The structure of CZS-0-1 was further confirmed by Top-down analysis of the oligosaccharides after oxidated hydrolysis by mass spectrometry. CZS-0-1 exhibited significant heparin-like anticoagulant activity. It exerted anticoagulant effects by inhibiting FIIa and FXa activities with the presence of heparin cofactors. The anticoagulant activity of CSZ-0-1 was closely related to the molecular weight, and the reduction of molecular weight may lead to a significant decrease in the anticoagulant activity. This study demonstrated that the green algae, Codium fragile can be considered as a useful resource for bioactive polysaccharides. [Display omitted] •A sulfated galactoarabinan CZS-0-1 was extracted from the green tide seaweed Codium fragile.•It had (1 → 3)-β-L-Arap with sulfate groups at O-4 or O-2 and partially branched at O-4 with β-D-Galp.•CZS-0-1 exhibited heparin-like anticoagulant activity.